Reflection of Tradition in Artist’s Writings, or Learning Anthropology from Stasys Eidrigevičius - Ivanauskaitė-Šeibutienė, Vita (Tautosakos darbai, 2018)
The subject of analysis comprises autobiographical texts by the famous artist Stasys Eidrigevičius (born in 1949), who is very popular both in Lithuania and abroad. In various published essays, travel experiences, reviews of cultural events, interviews and poetic texts the artist extensively describes his childhood and early youth spent in the Lepšiai village (close to Panevėžys in northern Lithuania) in the 1960s. The oral and written stories frequently repeated by Stasys Eidrigevičius, which could be summarized as narrative of home, present a true-to life and unpolished view of a single family life, preserving numerous details of the traditional living. The poem by Stasys Eidrigevičius “The Singing Head of the Rooster” published in 2016 and amply illustrated with drawings and photos (the author used to take numerous pictures of his family home and the family members from his teenager years onwards) receives special attention, since it poetically summarizes the artist’s narrative of home as a whole. The poem was published in its author’s native dialect, with parallel version in Lithuanian literary language, its inherent part being the sound recording containing the vocal reading by the author.Reflections of traditional life gleaned in Stasys Eidrigevičius’ texts not only constitute the main subject of analysis, but also encourage the author of the article to look deeper into the canonical image of the traditional Lithuanian culture, formed in the course of the two previous centuries. This canon rests on a rather romanticized festive side of the life of the “ancient Lithuanians” and definitely lacks in representing the routine, everyday part of the community life. Thus, the narrative of home constructed by the artist Stasys Eidrigevičius may be considered as supplementing the canonical representation of the Lithuanian traditional culture by adding considerable variety and colours.
Keywords: -